Characterization of the Physiological Displacement of the Aortic Arch Using Non-Rigid Registration and MR Imaging. (February 2017) - Nasr, B.; Le Ven, F.; Savean, J.; Ben Salem, D.; Nonent, M.; Gouny, P.; Visvikis, D.; Fayad, H.
Abstract : Objectives: The aim of this work was to study physiological aortic arch three-dimensional displacement using non-rigid registration methods and magnetic resonance imaging (MRI). Materials and methods: Ten healthy volunteers underwent thoracic MRI. Prospective cardiac gating was performed with a 3D turbo field echo sequence to obtain end-systolic and end-diastolic MR images. The rigid and elastic behavior between these two cardiac phases was detected and compared using either an affine or an elastic registration method. To assess reproducibility, a second MRI acquisition was performed 14 days later. Results: Affine registration between the end-systolic and end-diastolic MR images showed significant global translations of the aortic arch and the supra-aortic vessels in the x, y, and z directions (2.02 ± 1.6, −0.71 ± 1.1, and −1.21 ± 1.4 mm, respectively). Corresponding elastic registration indicated significant local displacement with a vector magnitude of 5.1 ± 0.89 mm for the brachiocephalic artery (BCA), of 4.26 ± 0.83 mm for the left common carotid artery (LCCA), and of 4.8 ± 0.86 mm for the left subclavian artery (LSCA). There was a difference in displacement between the supra-aortic trunks of the order of 2 mm. Vector displacement was not statistically different between the repeated acquisitions. Conclusions: The present results showed important deformations in the ostia of supra-aortic vessels during the cardiac cycle. It seems that aortic arch motions should be taken into account when designing and manufacturing fenestrated endografts. The elastic registration method provides more precise results, but is more complex and time-consuming than other methods.